1979
DOI: 10.1111/j.1399-3011.1979.tb01730.x
|View full text |Cite
|
Sign up to set email alerts
|

A LIPOPHILIC DERIVATIVE OF NEOCARZINOSTATIN A Polymer Conjugation of an Antitumor Protein Antibiotic*

Abstract: A lipophilic derivative of neocarzinostatin (NCS), an antitumor antibiotic, was prepared by reaction with a synthetic water‐soluble polymer, [(styrene)1˜3‐(maleic acid4˜7/anhydride1)]. The reaction was carried out at pH 8.6 for 3 h and aimed at modifying the two nonessential aming (of Ala‐1, ε‐amino of Lys‐20). The NCS‐polystyrene (SMANCS was a column of Sephadex G‐100 in 0.05 M ammonium bic and the main product was obtained as a single peak. The elemental and showed an increased C and a decreased N content. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

1984
1984
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(45 citation statements)
references
References 14 publications
(5 reference statements)
1
44
0
Order By: Relevance
“…26,27 Furthermore, the safety of SMA has been shown in humans, as it has been approved for use in the clinic, conjugated to neocarzinostatin, as a treatment for hepatocellular carcinoma. 28,29 Lastly, using SMA to form micelles has multiple advantages over other nanoformulations. These benefits include a simple and economical preparation, high recovery, and the ability to control not only the quantity of drug encapsulated but also its release rate.…”
mentioning
confidence: 99%
“…26,27 Furthermore, the safety of SMA has been shown in humans, as it has been approved for use in the clinic, conjugated to neocarzinostatin, as a treatment for hepatocellular carcinoma. 28,29 Lastly, using SMA to form micelles has multiple advantages over other nanoformulations. These benefits include a simple and economical preparation, high recovery, and the ability to control not only the quantity of drug encapsulated but also its release rate.…”
mentioning
confidence: 99%
“…The tumor concentration of blue albumin mounted to ~10-fold that in the blood at 145 h. This phenomenon was also demonstrated with radio-labeled plasma proteins, including transferrin (90 kDa) and IgG (160 kDa), whereas smaller proteins, such as neocarzinostatin (12 kDa) and ovomucoid (29 kDa), did not accumulate within tumors (1,8,10). Subsequent studies have confirmed that macromolecules with a molecular weight above the renal threshold (40 kDa) tend to accumulate preferentially in neoplastic tissues upon intravenous administration (1,11).…”
Section: Nanometer Size Rangementioning
confidence: 73%
“…SMA copolymers also have a long-standing history in life sciences, originally being described as conjugates for drugs in cancer therapy (Maeda et al 1979;Maeda 2001). Later, it was found that SMA can interact with phospholipids to form discoidal structures that can incorporate hydrophobic molecules and therefore would be useful as a drug delivery system ( 2001).…”
Section: The Styrene-maleic Acid Copolymermentioning
confidence: 99%